Phytoplankton abundance and diversity during a bloom of Pyrodinium bahamense in Cambatutay Bay, Samar, Philippines from September 2016 to January 2017 - Urbano, Yvonne C. (2017)
Harmful algal bloom (HAB), which is commonly known to many as "red tide" is a phenomenon caused by sudden blooms of microalgae such as Pyrodinium bahamense. In a recent red tide in Cambatutay Bay, several cases of Paralytic Shellfish Poisoning (PSP) have been reported. Therefore, it is imperative to monitor the ecological status of the surrounding waters. This study aimed to provide a list of the phytoplankton species present during the red tide occurrence in 2016, to determine the abundance of P. bahamense and to determine the physico-chemical parameters in Cambatutay Bay during the red tide. The collection of samples was conducted once a month from September 2016 to January 2017. A mean value of 29'C, 8.20, and 32.8 ppt was recorded for temperature, pH and salinity respectively. Moreover, the chlorophyll-a and nitrate concentration for the bay was found to have a mean value of 0.06 mg/L and 1.617uM respectively. A total of 61 phytoplankton species was recorded. Pyrodinium bahamense was found from all the sampling periods and was one of the most dominant species with a maximum of 5.0 x 10 raised to the power of 3 cells/L for the month of January. Dinophysis spp. had the highest mean cell density of 4.3 x 10 raised to the power of 3 cells/L. The most phytoplankton species was recorded on the month of January with a Shannon-Weiner diversity index of 3.93. Aside from P. bahamense, other potentially harmful phytoplankton species should be carefully monitored to further understand their ecology and predict harmful blooms and minimize ecological and human casualties.